Comparative Subsurface Characterization Of The Quaternary And Residual Sites In Northern Peninsular Malaysia By Cumulative SPT(N) For Assesing Concrete Pile Foundat - Besenun, Nur Farah Shahirah (Universiti Sains Malaysia, 2017)
The Northern Peninsular Malaysia area mostly consists of soft marine clays for coastal area. This marine clays are makes it challenging to construction activities. Meanwhile, northern area also consists of laterites soil but less develop compared to coastal sites. In this research, a new method of evaluating the quality of soils was introduced. Specifically, the standard penetration test (SPT) data were converted into the cumulative SPT(N) value curve for comparison between sites which is marine clays and laterites soil. SPT(N) value data obtained from Piezocone test from three marine clays sites and three from laterite sites were used and converted into cumulative SPT(N) value curves. The selected SPT(N) value reading were from the 1m intervals. The sites from marine clays will comparing to the sites from laterite soil. In this study, each marine clay site and laterites will be comparing each other with their actual depth from the data and also same depth for both sites (5m). The evaluation based on the range of cumulative SPT(N) values and shape of the curve which marine clays have steeper line graph compare to laterites. The cumulative SPT(N) value for laterites were higher than for marine clays sites. Thus, the evaluation of a site based on cumulative SPT(N) values was found more practical to be used in geotechnical practice. The cumulative SPT(N) method also expected to be able differentiate quality of sites in terms of foundation required. In this study, the evaluation of pile bearing capacity of a site will be involving the cumulative SPT(N) and also second cumulative SPT(N). A correlation of depth and total bearing capacity are produced. The length of soil penetration used are 5m and 10m under the ground and marine clays sites were chosen. The correlation of depth and total bearing capacity very useful to estimate suitable length of pile to be used in foundation design.